Development of the Generic Multifaceted Automaticity Scale (GMAS) and preliminary validation for physical activity. (July 2016) - Boiché, Julie; Marchant, Gonzalo; Nicaise, Virginie; Bison, Aline
Abstract: Objectives: This article presents the validation of a Generic Multifaceted Automaticity Scale (GMAS) assessing the automatic properties of habitual behaviours. Design: A quantitative approach was adopted within various adult samples in order to confirm the internal and external validity of the GMAS pertaining to Physical Activity (PA). Method: Study 1 investigated the content validity of a series of items among experts ( N = 13) and respondents ( N = 26). Study 2 examined the scale's construct validity for PA ( N = 293). Study 3 tested the GMAS external validity ( N = 161). Study 4 evaluated the internal consistency and predictive validity for the GMAS applied to transportation modes ( N = 167). Study 5 used a 1-week prospective design and included Theory of Planned Behaviour (TPB; Ajzen, 2012) variables in order to test the predictive validity of the GMAS for active transportation ( N = 125). Results: Study 1 supported the fact that the 9 items primarily reflected one facet of automaticity. Study 2 validated the hierarchical structure of the scale. In Study 3, convergent validity was confirmed regarding PA through significant correlations with the Self-Report Behavioural Automaticity Index (SRBAI; Gardner et al., 2012) and predictive validity was supported by significant correlations with self-report PA behaviour. Study 4 confirmed its internal consistency and predictive validity. Study 5 demonstrated that the scores derived from the GMAS significantly predicted active transportation behaviour, above and beyond TPB constructs. Discussion: The GMAS appears as a valid instrument for research on everyday PA behaviours. Highlights: The internal and external validity of the GMAS was supported for physical activity behaviours. The scale assesses three distinct facets of automaticity: lack of intention, lack of control, efficiency. The 9-item 3-factor hierarchical structure was attested and reliability was demonstrated. The automaticity scores derived from the GMAS are higher for frequently performed behaviours. The global automaticity score is related to active transportation, over and beyond intentions.